Prediktor Waktu Konversi Kultur Dahak Pada Pasien Tuberkulosis Resistan Obat Di Dki Jakarta Tahun 2020 - 2022 - Budiyani, Putri Immi Rizky; Djuwita, Ratna; Wahyono, Tri Yunis Miko; Handayani, Dwi (Syntax Literate, 2025)
Tuberculosis (TB) is an infectious disease that poses a global health problem, including in DKI Jakarta, which has a high burden of Drug-Resistant TB (DR-TB). Sputum culture conversion is an important indicator in monitoring TB treatment. This study aims to evaluate the time to sputum culture conversion and identify its predictors among DR-TB patients in DKI Jakarta from 2020 to 2022 using a retrospective cohort design. The analyzed variables include resistance type, initial sputum, age, gender, previous treatment history, HIV comorbidity, Diabetes Mellitus comorbidity, type of healthcare facility, and DR-TB treatment regimen. Out of 936 analyzed patients, 82.05% experienced sputum culture conversion with a cumulative survival probability at the end of observation of 11.01% and an overall median survival of 3 months. Six variables were identified as predictors of sputum culture conversion time: resistance type, initial sputum, age, previous treatment history, type of healthcare facility, and treatment regimen used. This study is expected to provide valuable information for TB programs and serve as a reference for future research.